The relationship between sustainability and deglobalization - Pennanen, Emil (My University, 2025)
The world is facing new challenges, as significant geopolitical events are constantly altering the global environment. Conflicts are dividing nations, and collaboration among international organizations is crumbling. Trade conflicts between major countries like the United States and China, along with protectionist measures worldwide, are prompting a move away from globalization. This trend of deglobalization signifies a broader dismissal of interconnectedness in support of domestic priorities, carrying important consequences for sustainability development. Since deglobalization itself is a relatively recent phenomenon, there is very limited prior research on its effects on sustainability. This thesis explores the connection between deglobalization and sustainability, highlighting how global crises, political decisions, and shifts in global value chains (GVCs) influence environmental, social, and economic aspects. The key research question guiding this study is: "How does deglobalization influence sustainability?" To answer this, the study is divided into two sub-questions. Initially defining deglobalization and the main factors contributing to it. This is accomplished by examining theoretical frameworks such as realism and liberalism, in conjunction with ongoing global phenomena driving deglobalization. Secondly, the thesis explores the concept of sustainability and investigates the backlash against globalization, finally assessing the consequences of deglobalization through environmental, social, and economic lenses. The findings indicate that the impact of deglobalization on sustainability is not inherently positive or negative. The relationship between the two is complex, and the impact significantly relies on multiple aspects. GVCs were found to be a key factor, both driving deglobalization and guiding its impact. They can either hinder or promote sustainability based on their restructuring and underlying motivations. Divergent political perspectives further influence the impact on sustainability, with realist-driven deglobalization posing challenges by undermining international collaboration, while liberal-driven initiatives may enhance sustainability by addressing globalization's flaws through cooperation rather than isolation. Policy implementation and local contexts greatly affect these dynamics, necessitating cooperation among stakeholders to rethink GVCs sustainably simultaneously supporting local economies. A key consideration in this process is equity, as developed nations must be mindful of not restricting opportunities for developing countries, ensuring that their policies do not hinder the growth and development of less affluent regions.

Maailma kohtaa uusia haasteita, kun merkittävät geopoliittiset tapahtumat muuttavat jatkuvasti globaalia ympäristöä. Konfliktit jakavat maita, ja kansainvälisten organisaatioiden yhteistyö on murenemassa. Kauppakiistat suurten maiden, kuten Yhdysvaltojen ja Kiinan välillä, sekä maailmanlaajuiset protektionistiset toimenpiteet ajavat siirtymistä pois globalisaatiosta. Tämä deglobalisaation suuntaus merkitsee maiden välisten siteiden hylkäämistä kotimaisten etujen tukemiseksi, ja sillä on merkittäviä vaikutuksia kestävään kehitykseen. Koska deglobalisaatio on suhteellisen uusi ilmiö, sen vaikutuksista kestävyyteen on hyvin vähän aikaisempaa tutkimusta. Tässä tutkimuksessa tarkastellaan deglobalisaation ja kestävyyden välistä yhteyttä, korostaen kuinka globaalit kriisit, poliittiset päätökset ja muutokset globaaleissa arvoketjussa vaikuttavat ympäristön, sosiaalisen ja taloudellisen ulottuvuuksien eri osa-alueisiin. Pääkysymys, joka ohjaa tätä tutkimusta, on: "Miten deglobalisaatio vaikuttaa kestävyyteen?" Tähän vastatakseen tutkimus jakautuu kahteen alakysymykseen. Aluksi määritellään deglobalisaatio ja sen keskeiset ajurit. Tämä tapahtuu tarkastelemalla teoreettisia viitekehyksiä, kuten realismia ja liberalismia, yhdessä meneillään olevien globaalien ilmiöiden kanssa, jotka ajavat deglobalisaatiota. Toiseksi tutkielma tarkastelee kestävyyden käsitettä ja tutkii globalisaation vastareaktioita, viimeisenä arvioiden deglobalisaation seurauksia ympäristöllisen, sosiaalisen ja taloudellisen näkökulman kautta. Tutkimustulokset osoittavat, että deglobalisaation vaikutus kestävyyteen ei ole itsessään positiivinen tai negatiivinen. Näiden kahden välinen yhteys on monimutkainen, ja vaikutus riippuu merkittävästi useista tekijöistä. Maiden väliset arvoketjut todettiin tärkeäksi tekijäksi, joka sekä ajaa deglobalisaatiota että ohjaa sen vaikutuksia. Ne voivat joko estää tai edistää kestävyyttä niiden rakenneuudistusten ja taustalla olevien motiivien mukaan. Eri poliittiset näkökulmat vaikuttavat myös kestävyyteen, sillä poliittisesti realistisesti motivoitunut deglobalisaatio luo haasteita heikentäen kansainvälistä yhteistyötä, kun taas liberaalit poliittiset aloitteet voivat edistää kestävyyttä käsittelemällä globalisaation puutteita yhteistyön kautta eristäytymisen sijaan. Politiikan toteutus ja paikalliset olosuhteet vaikuttavat näihin dynamiikkoihin, ja tämä edellyttää sidosryhmien yhteistyötä, jotta arvoketjuja voidaan uudelleen rakentaa kestävästi samanaikaisesti tukien paikallisia talouksia. Tässä prosessissa keskeinen huomioitava tekijä on tasa-arvo, sillä kehittyneiden maiden on tärkeää varmistaa, etteivät ne rajoita kehittyvien maiden mahdollisuuksia, ja että niiden politiikat eivät estä vähemmän vauraiden alueiden kasvua ja kehitystä.
Keywords: deglobalization, sustainability